Increasing the Production Capacity of Upland Food Crops - MULYANI, ANNY; HIDAYAT, ACHMAD (Indonesian Center for Agriculture Land Resource Development, 2009)
Upland agriculture plays an important role in producing various kinds of food crops. However, data of the annual upland crops areas that are needed as a basis for area extensification planning is not available. Therefore land area of 10 commodities of annual upland crops was estimated based on its comparison with paddy field areas, with the assumption of cropping index of 100 (one crop per year). For example, upland area planted to maize is assumed 60% of the total harvested area of maize, because the remaining 40% is produced in paddy field areas. Based on these predictions, the upland areas planted to 10 food crops is only about 5.53 million ha or 37.7% of the total annual upland agriculture area of 14.6 million ha. To evaluate the production capacity of the upland areas, we grouped those areas based on soil fertility and potential yield for each commodity. The results indicate that if the 5.53 million ha upland areas are used optimally for food crop production, it can produce 2.82 million tons of unhusked upland rice, 9.15 million tons of corn grain, 0.23 million tons of soybean grain, 0.73 million tons of peanuts pods, 0.20 million tons of mungbeans, 20.81 million tons of cassava, 0.58 million tons of sweet potato, 1.0 million tons of potatoes, 0.21 million tons of shallots and 1.3 million tons of sugarcane. If in the coming year, the total area of upland can be increased gradually from 37.7% to 70% of the total available annual upland areas, i.e. to about 10.2 million ha, thus the upland crops production capacity will increase to 4.9 million tons of upland rice , 16.2 million tons of corn, 0.4 million tons of soybeans, 1.5 million tons of peanuts, 0.35 million tons of mungbeans, 37.3 million tons of cassava, one million tons of sweet potatoes, 1.8 million tons of potato, 0.27 million tons of shallots and 2 million tons of sugarcane. By increasing the upland areas of about 5 million, it will lead to the national selfsufficiency of most commodities until the year of 2050, except for soybeans, potatoes and shallots. Therefore, to maintain selfsufficiency in rice and maize , as well as promote self-sufficiency of other food crop production, the extensification of upland agricultural areas for food crops is a prerequisite.